1977 Federal Budget ? ?The Balancing Act? - R. D. Brown (Canadian Institute of Mining, Metallurgy and Petroleum, 1977)
In his March 31, 1977 budget, Finance Minister Macdonald has attempted the delicate balancing act of stimulating the economy without reinforcing the inflationary pressures which Canada is continuing to experience. Several tax changes of benefit to the mining industry, as well as measures designed to encourage oil exploration in frontier areas, are among the budget proposals. Additional earned depletion of 66- 2 /3 %, which may be offset against income from any source, will be available on drilling costs in excess of $5 million incurred between March 31, 1977 and April 1, 1980 in connection with an exploratory well in Canada, including the continental shelf . Other changes include more favourable treatment of resource property dispositions, less restrictive rules r elating to "successor corporations" , increased capital-cost allowance on railway spur lines, the inclusion of certain production royalties in Canadian development expenses and the application of the lower "manufacturing and processing" tax rate to sulphur production. To encourage business capital spending, the 5% federal investment tax credit it to be extended an additional three years to mid 1980 and broadened to include spending on scientific research and development. The rate of credit will also be selectively increased on a regional basis, to 7.5 % in certain designated areas in Saskatchewan, Manitoba. Northern. Ontario and Quebec, and to 10% in the Atlantic provinces and the Gaspe.